2019
DOI: 10.1002/cne.24811
|View full text |Cite
|
Sign up to set email alerts
|

Afferent connections of the thalamic nucleus reuniens in the mouse

Abstract: The nucleus reuniens (RE) is part of the midline thalamus and one of the major sources of thalamic inputs to the hippocampal formation and the medial prefrontal cortex. However, it not only sends strong efferents to these areas but is also heavily innervated by both brain regions. Based on its connectivity and supported by functional studies the RE has been suggested to represent a major hub in reciprocal hippocampal–prefrontal communication. Indeed, inactivation studies have demonstrated that this nucleus is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…In the present study, these more superficial subiculum cells, although present, were only evident in substantial numbers, when the tracer injection spread beyond nucleus reuniens. The implication, that nucleus reuniens itself is principally innervated by very deep (perialvear) subiculum cells, is supported by two recent mouse studies (Bienkowski et al, 2018;Scheel et al, 2019; see also Mathiasen et al, 2019).…”
Section: Differentiated Layersmentioning
confidence: 89%
“…In the present study, these more superficial subiculum cells, although present, were only evident in substantial numbers, when the tracer injection spread beyond nucleus reuniens. The implication, that nucleus reuniens itself is principally innervated by very deep (perialvear) subiculum cells, is supported by two recent mouse studies (Bienkowski et al, 2018;Scheel et al, 2019; see also Mathiasen et al, 2019).…”
Section: Differentiated Layersmentioning
confidence: 89%
“…Other previous studies also suggested that Sol contributed to the therapeutic effect of acupuncture on inflammation, regulating the GI tract, and relieving pain [54][55][56][57] . The cingulate cortex receives neuronal information from the thalamus and the neocortex, and then projects them to other brain areas of the prefrontal cortex, amygdala, hippocampus, hypothalamus, and midbrain 58,59 . These interconnected prefrontallimbic networks are strongly involved in the formation and processing of emotion, learning, and memory, and these are related to acupuncture signaling transduction, controlling pain, and depression 38,39,60 .…”
Section: Discussionmentioning
confidence: 99%
“…A certain difference between mice and rats may exist in the organization of brain circuits’ connectivity. For instance, Scheel et al [ 37 ] described the interspecies differences regarding the integration of the nucleus reuniens (a part of the midline thalamus) in circuits of fear, aversion, and defense. The brain stress systems in rats and mice operate on the same bases, and across species there is some universal consistency with respect to brain regions expressing high levels of mineralocorticoid (MR) and glucocorticoid (GR) receptors in adulthood [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%